Rocking and kinematic analysis of two masonry church façades - Giresini, L (2016)
The paper deals with the application of two methods of local analysis on masonry structures. Rocking and kinematic analysis are applied to two cases study: a gable of the Ica Cathedral that survived the 2007 Pisco earthquake and a church façade connected to transverse walls, which collapsed in the 2012 Emilia Romagna earthquake. The critical aspects of both analysis are discussed and the differences in the outputs commented. Being the two rigid blocks at height different from zero, an amplification factor of the seismic record was calculated for performing the rocking analysis. The gable is treated as free-standing block whereas the upper part of the church façade is analyzed in the rocking analysis by accounting for the rebound effect caused by the transverse walls, through the stiffness of a bed spring.